Finding Satoyama – Forest bathing as a creative practice of knowledge creation and healing in/with/through damaged landscapes - Wuyts, Wendy (Journal of Ecohumanism, 2024)
Many people in the Western world are estranged from the more-than-human world, which negatively impacts their health and well-being. This article investigates the effect of forest bathing as an intervention on how designers and other citizens can reconnect with nature. Walking, talking, and sitting spot practices are not only research methods that help to understand the histories and interdependencies of a landscape and contribute to society and science, but can also be used as mental health promotion tools to generate self-care, especially when dealing with the experience of wounds through the inner and outer landscapes in which we engage. This article is based on an extensive review of a multidisciplinary body of literature. Although mainly conceptual, this article is empirically informed and illustrated by my experiences in Japan. By sharing an autoethnography of experiencing a Japanese landscape through five walks along the same trail over 1.5 years while exploring the deepening journey into the forest bathing practice, this article illustrates the opportunities and benefits of deploying forest bathing in landscape architecture and other regional and urban planning interventions. It also examines the concept of self-care and environmental citizenship and how they emerge in the forest bathing practice.